Problems of formation and valence of homonymous words for Uzbek and English languages - Geldiyeva Khursandoy (Peerian Journals Publishing, 2022)
We know that all languages have homonyms, synonyms, antonyms, paronyms and synonyms. It is important to distinguish these words from each other. We do not speak in world languages, we can say in Uzbek grammar, these words are also called by other names. For example, homonymous words have the same form but different meanings, synonyms have the same meaning, but synonyms have different meanings, paronyms differ in the same sound, and antonyms do not have the same meaning. We call null words and consonant words a group of horses. In many languages they are divided into spiritual groups as above. The valence of the word homonyms is the valence of all the words of the word homonyms that come with the word. This article provides information on some homonymous words and their valences in English and Uzbek.
Keywords: homonymous words; valence; synonyms; polysemous words